The temporal variations in principal and shallow-water tidal constituents and their application in tidal level calculation: an example in Zhoushan Archipelagoes with complex bathymetry. (15th April 2023) - Wei, Zilu; Jiao, Xiaohui; Du, Yunfei; Zhang, Jicai; Pan, Haidong; Wang, Guansuo; Wang, Daosheng; Wang, Ya Ping
Abstract: Temporal variations in tides are critical for ocean dynamics and engineering activities around coastal areas. Based on the data observed from 8 tide-gauge stations spanning 2 years (2016–2017), variations in principal (M2, S2, K1, O1 ) and shallow-water (M4, MS4, M6, 2MS6 ) tidal constituents in the Zhoushan Archipelagoes were studied by applying both classic and moving harmonic analysis methods. The temporal variations in the S2 and K1 harmonic parameters show annual cycles, while those of M2 and O1 are dominated by semi-annual cycles at most stations. The variations in shallow-water tides are more complex: larger discrepancies were observed among all stations and the variations in the harmonic parameters of the same constituent also varied differently. The phase lag variations were attributed mainly to changes in wind and runoff. Regarding the amplitude variations, the mean sea level and stratification played a considerable role; in addition, the effect of runoff on the semi-annual variation of amplitudes was significant. The predicted tidal levels and engineering water levels are improved when the temporal variations in harmonic parameters were considered, thereby benefiting practical application and related issues in coastal engineering and management. Highlights: The harmonic parameters have considerable temporal variations based on analysis of 2-year observed water levels in the Zhoushan Archipelagoes. The mechanisms of the temporal variations of amplitudes and phase lags are revealed. The differences in tidal levels calculation between constant and time-varying harmonic parameters are evaluated.